The hydrogen molecule H2 in inclined configuration in a weak magnetic field. (August 2019) - Alijah, Alexander; López Vieyra, Juan Carlos; Nader, Daniel J.; Turbiner, Alexander V.; Cobaxin, Héctor Medel
Highlights: Computation, for the first time, of two-dimensional potential energy surfaces, depending on the internuclear distance, R, and the inclination angle, θ of H2 in an external magnetic field. Use of physically adequate trial functions. Computation of the magnetic susceptibility for the first time at intermediate inclination. Computation of rovibrational states for H2 and D2 in an external magnetic field, first ever calculation in the literature. Abstract: Highly accurate variational calculations, based on a few-parameter, physically adequate trial function, are carried out for the hydrogen molecule H2 in inclined configuration, where the molecular axis forms an angle θ with respect to the direction of a uniform constant magnetic fieldB, for B = 0, 0.1, 0.175 and 0.2 a.u. Three inclinations θ = 0 ∘, 45 ∘, 90 ∘ are studied in detail with emphasis to the ground state 1 g . Diamagnetic and paramagnetic susceptibilities are calculated (for θ = 45 ∘ for the first time), they are in agreement with the experimental data and with other calculations. For B = 0, 0.1 and 0.2 a.u. potential energy curves E vs R are built for each inclination, they are interpolated by simple, two-point Padé approximant Pade [2/6]( R ) with accuracy of not less than 4 significant digits. Spectra of rovibrational states are calculated for the first time. It was found that the optimal configuration of the ground state for B ≤ B c r = 0.178 a.u. corresponds always to the parallel configuration, θ = 0, thus, it is a 1 Σ g state. The state 1 g remains bound for any magnetic field, becoming metastable for B > Bcr, while for Bcr < B < 12 a.u. the ground state corresponds to two isolated hydrogen atoms with parallel spins.